The Effect of Corn Substitution with Palm Kernel Meal Treated by Enzyme on Production Performance and Carcass Quality of Broiler - Muhammad Halim Natsir; Irfan Djunaidi; Osfar Sjofjan; Antonius Suwanto; Esti Puspitasari; Ludovika Jessica Virginia (Buletin Peternakan, 2018)
The research was aimed to evaluate the effects of substitution level of corn with palm kernel meal (PKM) untreated and palm kernel meal (PKM) treated by enzyme on production performance and carcass quality of broilers. The method used in this research was experiment using nested of completely randomized design with 2 factors, the main factor was type of palm kernel meal factors consisting of PKM without enzyme (B1) and PKM by mannanase enzyme (B2), and substitution corn level L0 (without substitution), L1 (12.5%), L2 (25%), L3 (37.5%) and L4 (50%). The different among the treatments were tested by Duncan’s multiple range test. The results showed that corn substitution with PKM untreated and PKM treated by enzymes was significantly effect (P<0.01) on feed conversion ratio (FCR), tenderness, meat cholesterol of broilers and income over feed cost (IOFC) and significant effect (P<0.05) on feed intake, but there is no significant difference on body weight, percentages of abdominal fat and water holding capacity (WHC). Furthermore, effect of level corn substitition with PKM nested to PKM untreated and PKM treated by enzyme was significantly effect (P<0.01) on feed intake, body weight, FCR, and tenderness and significant effect (P<0.05) on IOFC, but there is no effect on percentages of abdominal fat, WHC and meat cholesterol. It can be concluded that the corn substitution with PKM treated by enzymes was better than the PKM untreated on production performance and carcass quality of broilers. The optimal level of PKM untreated as corn substitution was 12.5%. While replacement with PKM treated by enzyme can be used up to 25%.